LPS adsorption and inflammation alleviation by polymyxin B-modified liposomes for atherosclerosis treatment - Huiwen Liu; Honglan Wang; Qiyu Li; Yiwei Wang; Ying He; Xuejing Li; Chunyan Sun; Onder Ergonul; Füsun Can; Zhiqing Pang; Bo Zhang; Yu Hu (Elsevier, 2023)
Chronic inflammation is critical in the onset and progression of atherosclerosis (AS). The lipopolysaccharide (LPS) level in the circulation system is elevated in AS patients and animal models, which is correlated with the severity of AS. Inspired by the underlying mechanism that LPS could drive the polarization of macrophages toward the M1 phenotype, aggravate inflammation, and ultimately contribute to the exacerbation of AS, LPS in the circulation system was supposed to be the therapeutic target for AS treatment. In the present study, polymyxin (PMB) covalently conjugated to PEGylated liposomes (PLPs) were formulated to adsorb LPS through specific interactions between PMB and LPS. In vitro, the experiments demonstrated that PLPs could adsorb LPS, reduce the polarization of macrophages to M1 phenotype and inhibit the formation of foam cells. In vivo, the study revealed that PLPs treatment reduced the serum levels of LPS and pro-inflammatory cytokines, decreased the proportion of M1-type macrophages in AS plaque, stabilized AS plaque, and downsized the plaque burdens in arteries, which eventually attenuated the progression of AS. Our study highlighted LPS in the circulation system as the therapeutic target for AS and provided an alternative strategy for AS treatment.